Temporal bone squamous cell carcinoma : A change in treatment - Vincent Ngu, Chien Ying; Mohd Sazafi, Mohd Saad; Tang, Ing Ping (Malaysian Medical Association, 2021)
SUMMARY Temporal bone squamous cell carcinoma (TBSCC) is a rare head and neck malignancy with the incidence 0.8 –1.0 cases in 1 million population. We are reporting a case series on the TBSCC cases that were operated on at Sarawak General Hospital, Malaysia. Ten patients were identified and collected with the presentation and type of surgery performed. It has been challenging for us to manage with recorded 2 years surviving in 6 out of 10 patients operated within this period. An adequate management with proper surgical resection of tumour and radiotherapy can extend the life expectancy for TBSCC patients